2002
DOI: 10.1016/s0960-9822(02)00892-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitotically Stable Association of Polycomb Group Proteins Eed and Enx1 with the Inactive X Chromosome in Trophoblast Stem Cells

Abstract: X inactivation in female mammals is one of the best studied examples of heritable gene silencing and provides an important model for studying maintenance of patterns of gene expression during differentiation and development. The process is initiated by a cis-acting RNA, the X inactive specific transcript (Xist). Xist RNA is thought to recruit silencing complexes to the inactive X, which then serve to establish and maintain the inactive state in all subsequent cell divisions. Most lineages undergo random X inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 31 publications
13
145
2
Order By: Relevance
“…However, the continued association of VRN1 with chromosomes all the way through mitosis was unexpected. Most Polycomb, Polycomb-associated proteins, and transcription factors have been found to be displaced from their recognition sequences during mitosis (43-47); however, some do remain, including Drosophila GAGA factor and Pipsqueak, which function as sequence-specific binding proteins and are involved in recruitment of Polycomb complexes to the Polycomb response element and high-mobility-group proteins, which bind DNA non-sequence-specifically (48)(49)(50)(51)(52). Knowledge of VRN1 interactors may help elucidate why it remains associated during mitosis and the significance of this finding for epigenetic stability of FLC silencing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the continued association of VRN1 with chromosomes all the way through mitosis was unexpected. Most Polycomb, Polycomb-associated proteins, and transcription factors have been found to be displaced from their recognition sequences during mitosis (43-47); however, some do remain, including Drosophila GAGA factor and Pipsqueak, which function as sequence-specific binding proteins and are involved in recruitment of Polycomb complexes to the Polycomb response element and high-mobility-group proteins, which bind DNA non-sequence-specifically (48)(49)(50)(51)(52). Knowledge of VRN1 interactors may help elucidate why it remains associated during mitosis and the significance of this finding for epigenetic stability of FLC silencing.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that loss of function of Eed in the mouse results in reactivation of the imprinted X chromosome in extraembryonic lineages 12 . Additionally, the Eed and Ezh2 proteins have been reported to co-localize with XIST on the imprinted X chromosome of mouse trophoblast stem cells 13 . Thus, we investigated whether Eed is also required for epigenetic regulation of autosomal imprinted loci.…”
Section: These Data Identify Eed As a Member Of A New Class Of Trans-mentioning
confidence: 99%
“…Both are controlled by a cis-acting X-inactivation center (Xic) (Brown et al 1991), a region that contains several noncoding RNA genes including Xist (Brockdorff et al 1992;Brown et al 1992) and the complementary Tsix gene (Lee et al 1999). During imprinted XCI, silencing is associated with the spread of Xist RNA along the paternal X chromosome (Mak et al 2002;Huynh and Lee 2003), while activity on the maternal X chromosome is preserved by expression of Tsix (Lee 2000;Sado et al 2001). Random XCI is also ini-tiated by Xist expression and blocked by Tsix.…”
Section: Two Forms Of X-chromosome Inactivation In the Mousementioning
confidence: 99%
“…In the extraembryonic tissues, as represented by trophoblast stem (TS) cells, the gradient of silencing along the X P disappears and all genes tested along the X P exhibit complete silencing (Huynh and Lee 2003). A more global pattern of inactivation in postimplantation cells may naturally follow from increased recruitment of heterochromatic factors such as the polycomb group proteins (Mak et al 2002(Mak et al , 2004Okamoto et al 2004), macroH2A1 (Costanzi et al 2000), and DNA methylation, all of which serve to "lock in" the inactive state. Thus, imprinted XCI is characterized by two distinct phases-one in the preimplantation embryo, where dosage compensation favors maternal transcription without precluding leaky paternal expression, and one in the postimplantation embryo, where the imperfection of the earlier form gives way to a globalized paternal silencing mechanism.…”
Section: Recent Advances: Evidence For a Silent X P In Preimplantatiomentioning
confidence: 99%
See 1 more Smart Citation